Hubungan Mutu Pelayanan Asuhan Keperawatan Dengan Kepuasan Pasien Di Ruang Rawat Inap Bougenville RSUD dr. Murjani Sampit - Suryagustina Suryagustina; Tomi Satalar; Sarmawati Sarmawati (Jurnal Ventilator, 2024)
The quality of nursing care services is a form of professional service and an integral part of healthcare. Patient satisfaction with nursing care is when patients and their families feel that everything meets their expectations. The current phenomenon is that some patients still report not receiving optimal nursing care, lack of communication in providing services, leading to dissatisfaction during their hospital stay. The aim of this research is to determine the relationship between the quality of nursing care services and patient satisfaction in the Bougenville Inpatient Room at dr. Murjani Regional General Hospital Sampit. The research method uses a correlation research design with a cross-sectional method. The instruments used in this study were questionnaires and the Rank Spearman statistical test aimed at 66 patients in the Bougenville Inpatient Room at dr. Murjani Regional General Hospital Sampit. The Spearman rho test result is 1.000, and the P-value is 0.000, which means the alpha value is 0.05, indicating that H1 is accepted. Therefore, there is a positive and significant relationship between the quality of nursing care services and patient satisfaction. The conclusion of this study is that there is a relationship between the quality of nursing care services and patient satisfaction in the Bougenville Inpatient Room at dr. Murjani Regional General Hospital Sampit. It is recommended for dr. Murjani Regional General Hospital Sampit to evaluate service satisfaction, especially improving the quality of nursing care services in the Bougenville Room.